The Pine Branch, Spring 1966 - (:unkn) unknown (Valdosta, Ga. : Creative Writing Club of Valdosta State College., 1966)
The Pine Branch. Periodical magazine. Created and published by the Creative Writing Club, English and Art Department, Valdosta State College. Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
Cover Earl Willis | Woodcut Wayne Overstreet 2 | Poems Scott Cohen 2 | Woodcut Gail Allen 4 | The Sun Scott Cohen 5 | Woodcut David Strickland 5 | What Can I Do? Scott Cohen 6 | Linoleum Cut Mary Williams 6 | Portrait of a Bose Donna Spratlin 8 | Spring Dying Edith Moore 9 | Linoleum Cut Mary Williams 9 | We Die Within Ourselves Gail Allen 1 0 | Linoleum Cut Bobert Stump 10 | Time Gail Allen 1 1 | Van Gogh Mike Nelson 1 2 | Photography Bobert Winter 1 3 | I Have But a Flower Milton Hamlin 1 7 | Linoleum Cut Robert Stump 1 7 | Two Reflections and a Becollection Gerald Joiner 18 | Woodcut L B B, I l l - 19 | Words of Mr Joyce Eddie Vickers ? 2 0 | Woodcut B C K e l l e y 21 | The Fourth Shadow Eddie Vickers 2 1 | The Hospital Cemetery Eddie Vickers 22 | Winter Warmth Terry Carter 23 | Woodcut Balph Sanford 23 | Poems From the Virgin Islands Boger S a u l s | Linoleum Cut Mary Williams | Turtle in a White Balloon James Lineberger 26 | Woodcut Judie Lester 26 | Poems James Lineberger ^ | The Basic Oneness Gail Allen 28 | Woodcut Gail Allen |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Valdosta State College; Valdosta; Schools--Georgia; Education